2019
DOI: 10.1002/cssc.201901813
|View full text |Cite
|
Sign up to set email alerts
|

Cu2O Nanocrystals‐Catalyzed Photoredox Sonogashira Coupling of Terminal Alkynes and Arylhalides Enhanced by CO2

Abstract: Herein the first visible-light-activated Sonogashira CÀCc oupling reaction at room temperature catalyzed by single-metal heterogeneous Cu 2 Ot runcated nanocubes (Cu 2 OT NCs) was developed. Aw ide varietyo fa ryl halidesa nd terminal alkynes workedw ell in this recyclable heterogeneous photochemical process to form the corresponding Sonogashira CÀCc oupling products in good yields. Mechanistic control studies indicated that CO 2 enhances the formation of light-absorbing heterogeneous surface-bound Cu I -pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…The size distribution analysis using the dynamic light scattering (DLS) technique reveals an average particle size of ∼293.6 nm. The polydispersibility index (PDI) value is 0.118, which clearly indicates that plasmonic CuO/Cu 2 O TNCs are moderately monodispersed (please refer to our previous publication) . The UV–vis–NIR absorption spectrum of plasmonic CuO/Cu 2 O TNCs displayed broad absorption up to 1800 nm, covering the NIR-I (650–950 nm), -II (980–1350 nm), and -III (1550–1800 nm) biological windows, respectively (Figure (D)).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…The size distribution analysis using the dynamic light scattering (DLS) technique reveals an average particle size of ∼293.6 nm. The polydispersibility index (PDI) value is 0.118, which clearly indicates that plasmonic CuO/Cu 2 O TNCs are moderately monodispersed (please refer to our previous publication) . The UV–vis–NIR absorption spectrum of plasmonic CuO/Cu 2 O TNCs displayed broad absorption up to 1800 nm, covering the NIR-I (650–950 nm), -II (980–1350 nm), and -III (1550–1800 nm) biological windows, respectively (Figure (D)).…”
Section: Resultsmentioning
confidence: 61%
“…It was reported that the bandgap of a p-type semiconductor CuO is 1.3–1.6 eV, which is lower than the corresponding bandgap of Cu 2 O (2.0 eV) . Very recently, we have reported the visible-light-activated Sonogashira C–C coupling reaction at room temperature catalyzed by single-metal heterogeneous Cu 2 O truncated nanocubes (Cu 2 O TNCs) . It is possible that CuO/Cu 2 O will form a type II band structure and eventually improve the photocatalytic activities by enhancing the charge separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties are strongly influenced by their morphology, phase and surface characteristics. Their potential application in various fields such as catalysis (Shanmugam et al, 2020), non-linear optics (Chen et al, 2014), photoelectrochemistry (Hao et al, 2020), light emitting diodes (Chen et al, 2020) and biosensing (Yue et al, 2020) is dependent on the ability to manipulate these properties by controlling their size, shape and phase.…”
Section: Introductionmentioning
confidence: 99%
“…[156][157][158][159][160][161] A recent study showed that when Cu 2 O nanocrystals with truncated nanocube morphology were used for the photocatalytic Sonogashira reaction in the presence of the K 2 CO 3 and CO 2 atmosphere, a CuO layer was formed in the exposed crystal surface. 161 Another fascinating hybrid photocatalyst where the Cu 2 O nanocube was decorated with SnO 2 nanoparticles showed a unique post-illumination photocatalytic "memory" effect, which means it can still be catalytically active in the dark aer the illumination was switched off for a certain period of time. 154 This "memory effect" was possible due to the presence of reversible chemical states (Sn 2+ vs. Sn 4+ ) in SnO 2 .…”
Section: Photocatalytic Organic Reactionsmentioning
confidence: 99%